Co-based alloys and their powders

A Co-based alloy with optimized C, Cr, W, Si, Mn, Cu, Fe, Ni, and Mo composition, along with a Cu-dissolved matrix and carbides, addresses toughness and corrosion resistance issues, achieving superior performance.

JP7602338B2Active Publication Date: 2024-12-18SANYO SPECIAL STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020152756
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-11
Publication Date
2024-12-18
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

Existing Co-based alloys suffer from insufficient toughness, hardness, and corrosion resistance, as highlighted in JP-A-2001-288521, JP 2016-7632, and JP2020-63495.

Method used

A Co-based alloy composition with specific ranges of C, Cr, W, Si, Mn, Cu, Fe, Ni, and Mo, along with a metal structure containing a Cu-dissolved matrix and carbides, including ε and γ phases, to enhance toughness, hardness, and corrosion resistance.

Benefits of technology

The alloy achieves excellent corrosion resistance, toughness, and hardness, making it suitable for various applications requiring these properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602338000001
    Figure 0007602338000001
  • Figure 0007602338000002
    Figure 0007602338000002
  • Figure 0007602338000003
    Figure 0007602338000003
Patent Text Reader

Abstract

To provide a Co-based alloy that can give a molding having excellent corrosion resistance, toughness and hardness.SOLUTION: A Co-based alloy contains C: 1.00 mass% or more and 3.00 mass% or less, Cr: 25.0 mass% or more and 34.0 mass% or less, W: 3.0 mass% or more and 15.0 mass% or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01 mass% or more and 1.00 mass% or less, Cu: 0.50 mass% or more and 6.00 mass% or less, Fe: 0 mass% or more and 10.00 mass% or less, Ni: 0 mass% or more and 15.00 mass% or less, and Mo: 0 mass% or more and 15.00 mass% or less, with the balance being Co and inevitable impurities. The Co-based alloy has a metallographic structure having a matrix containing Cu in a solid state. In the matrix, the ratio (Pcu) of Cu contained therein in a solid state is 1.0 mass% or more and 3.5 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Co-based alloy suitable for methods such as melting, powder metallurgy, powder cladding, laser cladding, and powder extrusion. [Background technology]

[0002] Co-based alloys generally have excellent corrosion resistance, and various improvements on these Co-based alloys have been proposed.

[0003] JP 2001-288521 A discloses a Co-based alloy containing C, Si, Cr, W, Fe, Ni, Mo, and W. In the metal microstructure of this Co-based alloy, eutectic carbides are dispersed in a matrix. The eutectic carbides are granular or lumpy. The grain size of the eutectic carbides is 30 μm or less. This metal structure is achieved by plastic working. This Co-based alloy has excellent corrosion resistance and wear resistance.

[0004] JP 2016-7632 A discloses a Co-based alloy containing Ni, Mn, Fe, C, Si, Cr, and Mo. These elements can contribute to cavitation erosion resistance. These elements can also contribute to toughness.

[0005] JP 2020-63495 A discloses a Co-based alloy containing C, Cr, W, Si, Mn, Fe, and Ni. This Co-based alloy has excellent corrosion resistance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2001-288521 A [Patent Document 2] JP2016-7632A [Patent Document 3] Patent Publication No. 2020-63495 Summary of the Invention [Problem to be solved by the invention]

[0007] The Co-based alloy disclosed in JP 2001-288521 A has insufficient toughness. The Co-based alloy disclosed in JP 2016-7632 A has insufficient hardness. The Co-based alloy disclosed in JP 2020-63495 A has room for improvement in corrosion resistance.

[0008] An object of the present invention is to provide a Co-based alloy from which a molded product having excellent corrosion resistance, toughness and hardness can be obtained. [Means for solving the problem]

[0009] The Co-based alloy according to the present invention has C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 15.0% by mass or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Cu: 0.50 mass% or more and 6.00 mass% or less, Fe: 0% by mass or more and 10.00% by mass or less, Ni: 0 mass% or more and 15.00 mass% or less, and Mo: 0 mass% or more and 15.00 mass% or less The balance is Co and unavoidable impurities. The Co-based alloy has a metal structure including a matrix in which Cu is dissolved. The proportion Pcu of Cu dissolved in the matrix is ​​1.0 mass % or more and 3.5 mass % or less.

[0010] The metallographic structure may include an ε phase having a hcp structure. Preferably, the volume fraction Pε of the ε phase relative to the entire metallographic structure is 60.0% or less.

[0011] This metal structure is (1) Matrix and (2) Carbide dispersed in the matrix This matrix (1) may have the following structure: (1-1) γ phase, which has an fcc structure and / or (1-2) ε phase, which has the hcp structure The carbide (2) includes (2-1) M6C carbide (2-2)M7C3 carbide and (2-3)M23C6 carbide The volume fraction Pc of carbides relative to the entire metal structure is 12.0% or more and 50.0% or less.

[0012] In another aspect, the powder material according to the present invention is a Co-based alloy. C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 15.0% by mass or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Cu: 0.50 mass% or more and 6.00 mass% or less, Fe: 0% by mass or more and 10.00% by mass or less, Ni: 0 mass% or more and 15.00 mass% or less, and Mo: 0 mass% or more and 15.00 mass% or less The balance is Co and unavoidable impurities. The Co-based alloy has a metal structure including a matrix in which Cu is dissolved. The proportion Pcu of Cu dissolved in the matrix is ​​1.0 mass % or more and 3.5 mass % or less. Effect of the Invention

[0013] The compact obtained from the Co-based alloy according to the present invention is excellent in corrosion resistance, toughness and hardness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the present invention will be described in detail based on preferred embodiments with reference to the drawings as appropriate.

[0015] The Co-based alloy according to the present invention contains C, Cr, W, Si, Mn, and Cu. The alloy may further contain Fe, Ni, or Mo. The balance is Co and unavoidable impurities. The metal structure of the Co-based alloy may contain a matrix and carbides dispersed in the matrix. The role of each element in the alloy will be described in detail below.

[0016] [Cobalt (Co)] Co is the main component of the matrix. At room temperature, the stable crystal structure of Co alone is a hexagonal close packed structure (hcp). At temperatures of 690K or higher, the stable crystal structure of Co alone is a face-centered cubic lattice (fcc). In the alloy according to the present invention, the matrix may have a γ phase and an ε phase. The crystal structure of the γ phase is fcc. The crystal structure of the ε phase is hcp.

[0017] [Carbon (C)] C combines with Cr and W to form carbides. These carbides can contribute to high hardness of the alloy. From this viewpoint, the C content is preferably 1.00 mass% or more, more preferably 1.30 mass% or more, and particularly preferably 1.50 mass% or more. Excess C impairs the toughness of the alloy. From the viewpoint of excellent toughness, the C content is preferably 3.00 mass% or less, more preferably 2.50 mass% or less, and particularly preferably 1.80 mass% or less.

[0018] Chromium Cr combines with C to form carbides. These carbides can contribute to the room temperature hardness, high temperature hardness, wear resistance, and corrosion resistance of the alloy. From these viewpoints, the Cr content is preferably 25.0 mass% or more, more preferably 27.0 mass% or more, and particularly preferably 28.0 mass% or more. Excess Cr impairs toughness. Furthermore, excess Cr leads to the formation of excess ε phase. This ε phase impairs the corrosion resistance of the molded product. From the viewpoints of toughness and corrosion resistance, the Cr content is preferably 34.0 mass% or less, more preferably 32.0 mass% or less, and particularly preferably 31.0 mass% or less.

[0019] [Tungsten (W)] W combines with C to form carbides. These carbides can contribute to high-temperature hardness and wear resistance. From these viewpoints, the W content is preferably 3.0 mass% or more, more preferably 6.0 mass% or more, and particularly preferably 8.0 mass% or more. Excess W impairs the toughness of the alloy. From the viewpoint of toughness, the W content is preferably 15.0 mass% or less, more preferably 12.0 mass% or less, and particularly preferably 10.0 mass% or less.

[0020] [Silicon (Si)] Si can contribute to the corrosion resistance and machinability of the alloy. From this viewpoint, the Si content is preferably 0.01 mass% or more, more preferably 0.50 mass% or more, and particularly preferably 0.90 mass% or more. Excessive Si impairs the toughness of the alloy. From the viewpoint of toughness, the Si content is preferably 2.00 mass% or less, more preferably 1.50 mass% or less, and particularly preferably 1.30 mass% or less.

[0021] [Manganese (Mn)] Mn generates a γ phase. This γ phase can contribute to the toughness of the alloy. From this viewpoint, the Mn content is preferably 0.01 mass% or more, more preferably 0.10 mass% or more, and particularly preferably 0.20 mass% or more. Excess Mn inhibits the strength of the alloy. From the viewpoint of strength, the Mn content is preferably 1.00 mass% or less, more preferably 0.80 mass% or less, and particularly preferably 0.50 mass% or less.

[0022] Copper (Cu) Cu is an extremely important element in the Co-based alloy according to the present invention. As is clear from the binary phase diagram of Co-Cu, Cu is hardly dissolved in the Co matrix at room temperature. On the other hand, according to the knowledge obtained by the present inventor, in the alloy according to the present invention, about 2% of Cu can be dissolved in the matrix. Therefore, Cu can contribute to the corrosion resistance of the alloy. From this viewpoint, the content of Cu is preferably 0.50 mass% or more, more preferably 0.80 mass% or more, and particularly preferably 1.00 mass% or more. According to the knowledge obtained by the present inventor, in an alloy with an excessive amount of Cu, a Cu phase precipitates. This Cu phase inhibits the hardness of the alloy. From the viewpoint of hardness, the content of Cu is preferably 6.00 mass% or less, more preferably 4.00 mass% or less, and particularly preferably 2.00 mass% or less.

[0023] [Iron (Fe)] Fe can contribute to the workability of the molded product. From this viewpoint, the Fe content is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and particularly preferably 0.05 mass% or more. Excess Fe impairs the corrosion resistance of the alloy. From the viewpoint of corrosion resistance, the Fe content is preferably 10.0 mass% or less, more preferably 7.0 mass% or less, and particularly preferably 5.0 mass% or less. The Co-based alloy may have a composition that does not substantially contain Fe. In other words, the preferred Fe content is 0 mass% or more and 10.0 mass% or less.

[0024] [Nickel (Ni)] Ni dissolves in the matrix and enhances the corrosion resistance of the alloy. From this viewpoint, the Ni content is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and particularly preferably 0.05 mass% or more. Excess Ni inhibits the hardness of the alloy. From the viewpoint of hardness, the Ni content is preferably 15.0 mass% or less, more preferably 10.0 mass% or less, and particularly preferably 5.0 mass% or less. The Co-based alloy may have a composition that is substantially free of Ni. In other words, the preferred Ni content is 0 mass% or more and 15.0 mass% or less.

[0025] [Molybdenum (Mo)] Mo combines with C to form carbides. According to the findings of the present inventors, the carbides contribute to hardness and wear resistance. According to the findings of the present inventors, Mo dissolved in the matrix suppresses dissolution of the matrix in a hydrochloric acid environment and a hydrofluoric acid environment. In other words, Mo also contributes to corrosion resistance. Mo can further be dissolved in the matrix to contribute to the corrosion resistance of the matrix. From the viewpoints of hardness, wear resistance, and corrosion resistance, the Mo content is preferably 0.10 mass% or more, more preferably 0.50 mass% or more, and particularly preferably 1.00 mass% or more. Excess Mo inhibits the toughness of the alloy. From the viewpoint of toughness, the Mo content is preferably 15.00 mass% or less, more preferably 10.00 mass% or less, and particularly preferably 6.00 mass% or less. The Co-based alloy may have a composition that does not substantially contain Mo. In other words, the preferred Mo content is 0 mass% or more and 15.0 mass% or less.

[0026] [Mo / C] A part of Mo is consumed to form carbides, and the remaining Mo dissolves in the matrix. The ratio of the mass content of Mo to the mass content of C is preferably 1.3 or more. In a Co-based alloy in which this ratio is 1.3 or more, a sufficient amount of Mo dissolves in the matrix. This Co-based alloy has excellent corrosion resistance. From this viewpoint, this ratio is more preferably 1.8 or more, and particularly preferably 2.3 or more. This ratio is preferably 10.0 or less.

[0027] Oxygen In the Co-based alloy according to the present invention, O is an unavoidable impurity. From the viewpoint of the corrosion resistance of the alloy, the mass content of O is preferably 200 ppm or less, more preferably 150 ppm or less, and particularly preferably 100 ppm or less.

[0028] [Aluminum (Al)] In the alloy of the present invention, Al is an inevitable impurity. Al can combine with Ti or Ni to form an intermetallic compound. This intermetallic compound impairs the toughness of the alloy. From the viewpoint of toughness, the Al content is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and particularly preferably 0.35 mass% or less.

[0029] [Titanium (Ti)] In the alloy of the present invention, Ti is an inevitable impurity. Ti can combine with Al or Ni to form an intermetallic compound. This intermetallic compound impairs the toughness of the alloy. From the viewpoint of toughness, the Ti content is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and particularly preferably 0.35 mass% or less.

[0030] [Metal structure] The metal structure of Co-based alloys is as follows: (1) Matrix and (2) Carbides dispersed in this matrix It has.

[0031] [Matrix] As described above, Cu is dissolved in the matrix. The matrix in which Cu is dissolved has excellent corrosion resistance. From the viewpoint of corrosion resistance, the ratio Pcu of the amount of Cu dissolved in the matrix to the total amount of the matrix is ​​preferably 1.0 mass% or more, more preferably 1.2 mass% or more, and particularly preferably 1.5 mass% or more. If the ratio Pcu is excessive, a Cu phase precipitates in the matrix. This Cu phase inhibits the hardness of the alloy. From the viewpoint of hardness, the ratio Pcu is preferably 3.5 mass% or less, more preferably 3.0 mass% or less, and particularly preferably 2.5 mass% or less.

[0032] Matrix (1) is, (1-1) γ phase, which has an fcc structure and / or (1-2) ε phase, which has a hcp structure Contains:

[0033] [ε phase] The ε phase is inferior in toughness. If the amount of the ε phase is too large, the durability and machinability of the molded product are impaired. From these viewpoints, the volume fraction Pε of the ε phase is preferably 60.0% or less of the entire metal structure, more preferably 40.0% or less, and particularly preferably 20.0% or less. The volume fraction Pε (%) is calculated by the following formula. Pε = Xε 100 In this formula, Xε is the volume ratio of the ε phase. The volume ratio Xε is calculated by the following formula.

[0034]

number

[0035] [carbide] The metal structure of Co-based alloys may contain the following carbides (2): (2-1) M6C carbide (2-2)M7C3 carbide and (2-3)M23C6 carbide Examples of M6C-based carbides include Co3W3C. Examples of M7C3-based carbides include Cr7C3. Examples of M23C6-based carbides include Cr23C6. The metal structure may include all of the M6C-based carbides, M7C3-based carbides, and M23C6-based carbides, or may include any two of them, or may include any one of them.

[0036] M6C carbides, M7C3 carbides and M23C6 carbides are not easily dissolved in hydrochloric acid. An alloy containing an appropriate amount of these carbides has excellent corrosion resistance. From the viewpoint of corrosion resistance, the total volume fraction Pc of M6C carbides, M7C3 carbides and M23C6 carbides with respect to the entire metal structure is preferably 12.0% or more, more preferably 15.0% or more, and particularly preferably 17.0% or more. Excessive carbides impair the toughness of the alloy. From the viewpoint of toughness, the volume fraction Pc is preferably 50.0% or less, more preferably 40.0% or less, and particularly preferably 35.0% or less. The volume fraction Pc (%) is calculated by the following formula. Pc = Xc 100 In this formula, Xc is the volume ratio of the carbide. The volume ratio Xc is calculated by taking a backscattered electron image of the cross-sectional structure of the compact (sintered compact). Image analysis software is used for this calculation.

[0037] [Alloy manufacturing] The Co-based alloy according to the present invention can be produced by a melting method, a casting method, a powder metallurgy method, a pulverization method, etc. From the viewpoint of toughness of the alloy, the powder metallurgy method is preferred. The powder used in the powder metallurgy method is preferably obtained by an atomization method.

[0038] [Powder] The present invention is also directed to a powder. The material of the powder according to the present invention is the above-mentioned Co-based alloy. This Co-based alloy is: C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 15.0% by mass or less, Si: 0.01 mass% or more and 2.00 mass% or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Cu: 0.50 mass% or more and 6.00 mass% or less, Fe: 0% by mass or more and 10.00% by mass or less, Ni: 0 mass% or more and 15.00 mass% or less, and Mo: 0 mass% or more and 15.00 mass% or less The remainder is Co and unavoidable impurities. This Co-based alloy has a metal structure including a matrix in which Cu is dissolved. The ratio Pcu of Cu dissolved in this matrix is ​​1.0 mass% or more and 3.5 mass% or less. EXAMPLES

[0039] The effects of the present invention will be clarified by the following examples, but the present invention should not be construed as being limited based on the description of these examples.

[0040] [Examples 1-14 and Comparative Examples 19-31] A metal having a predetermined composition was melted to obtain a molten metal. The molten metal was melted in an inert gas atmosphere and subjected to nitrogen gas atomization to obtain a powder. The powder was subjected to classification to adjust the particle size to 500 μm or less. The powder was filled into a capsule, and the capsule was sealed. The powder was subjected to hot isostatic pressing (HIP) at 1170° C. to obtain the bulks of Examples 1-14 and Comparative Examples 19-31.

[0041] [Examples 31-33] The bulk of Examples 15-18 was obtained by a melting method using an arc melting method.

[0042] [Measurement of ratio Pcu] A test piece (10 mm x 10 mm x 14 mm) was obtained from the bulk. This test piece was observed with a scanning electron microscope (SEM). EDS analysis was performed on the matrix region using a backscattered electron image at 4000 times magnification to obtain the ratio Pcu of the amount of Cu dissolved in the matrix. The results are shown in Table 1-3 below.

[0043] [hardness] The bulk Rockwell hardness (HRC) was measured, and the results are shown in Tables 1-3 below. A hardness of 45 HRC or greater is preferred.

[0044] [Shock value] A test piece (10R2mmC notch) was obtained from the bulk. The test piece was subjected to a Charpy impact test to measure the impact value. The results are shown in Table 1-3 below. The impact value was 5J / cm 2 An alloy having the above properties has excellent toughness.

[0045] [Corrosion resistance] A test piece (10 mm x 10 mm x 14 mm) was obtained from the bulk. This test piece was subjected to a corrosion resistance test. The test conditions were as follows. Solution: 10% hydrochloric acid aqueous solution Temperature: 40℃ Duration: 10 hours The corrosion rate was calculated by dividing the corrosion weight loss by the surface area of ​​the test piece before the test and the time. The results are shown in Table 1-3 below. 2 It is preferable that the thickness is less than or equal to .h.

[0046] [Table 1]

[0047] [Table 2]

[0048] [Table 3]

[0049] In the alloy according to Comparative Example 19, the volume fraction Pc of carbides is small because the amount of C is too small, and therefore the hardness of this alloy is insufficient.

[0050] In the alloy according to Comparative Example 20, the volume fraction Pc of carbides is large due to an excess of C. Therefore, the toughness of this alloy is insufficient.

[0051] The alloy according to Comparative Example 21 has an insufficient Cr content, and therefore the hardness and corrosion resistance of this alloy are insufficient.

[0052] In the alloy of Comparative Example 22, Cr is excessive, and therefore the toughness of this alloy is insufficient.

[0053] In the alloy of Comparative Example 23, the amount of W is too small, and therefore the hardness of this alloy is insufficient.

[0054] The alloy of Comparative Example 24 contains an excessive amount of W. Therefore, this alloy does not have sufficient toughness.

[0055] The alloy of Comparative Example 25 contains an excess of Si, and therefore the toughness of this alloy is insufficient.

[0056] In the alloy of Comparative Example 26, Mn is excessive, and therefore the toughness of this alloy is insufficient.

[0057] The alloy of Comparative Example 27 contains an excessive amount of ε phase due to an insufficient amount of Cu, and therefore the corrosion resistance of this alloy is insufficient.

[0058] In the alloy of Comparative Example 28, Cu is excessive, and therefore the hardness of this alloy is insufficient.

[0059] The alloy of Comparative Example 29 contains an excess of Fe, and therefore the corrosion resistance of this alloy is insufficient.

[0060] In the alloy of Comparative Example 30, Ni is excessive, and therefore the hardness of this alloy is insufficient.

[0061] In the alloy of Comparative Example 31, Mo is excessive, so the volume fraction Pc of carbides is large, and therefore the toughness of this alloy is insufficient.

[0062] The alloys according to Examples 1 to 18 are excellent in various properties. From these results, the superiority of the present invention is clear. [Industrial Applicability]

[0063] The Co-based alloys described above are suitable for a variety of applications requiring corrosion resistance.

Claims

1. C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 10.0% by mass or less, Si: 0.01% by mass or more and 2.00% by mass or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Cu: 0.50% by mass or more and 6.00% by mass or less, Fe: 0% by mass or more and 10.00% by mass or less, Ni: 0% by mass or more and 10.00% by mass or less, and Mo: 0% by mass or more and 15.00% by mass or less Contains The balance is Co and unavoidable impurities, The alloy has a metal structure including a matrix in which Cu forms a solid solution, A Co-based alloy in which a ratio Pcu of Cu dissolved in the matrix is ​​1.5 mass % or more and 3.5 mass % or less.

2. The metal structure includes an ε phase having an h.c.p. structure, 2. The Co-based alloy according to claim 1, wherein a volume fraction Pε of the ε phase with respect to the entire metal structure is 60.0% or less.

3. The metal structure is (1) Matrix and (2) Carbide dispersed in the matrix It has The matrix (1) is (1-1) γ phase, which is a phase having an f.c.c. structure and / or (1-2) ε phase, which is a phase having an h.c.p. structure Contains The carbide (2) (2-1) M6C carbide (2-2) M7C3 carbide and (2-3) M23C6 carbide The composition includes one or more selected from the group consisting of 3. The Co-based alloy according to claim 1, wherein a volume fraction Pc of the carbides relative to the entire metal structure is 12.0% or more and 50.0% or less.

4. The material is a Co-based alloy, The Co-based alloy is C: 1.00% by mass or more and 3.00% by mass or less, Cr: 25.0% by mass or more and 34.0% by mass or less, W: 3.0% by mass or more and 10.0% by mass or less, Si: 0.01% by mass or more and 2.00% by mass or less, Mn: 0.01% by mass or more and 1.00% by mass or less, Cu: 0.50% by mass or more and 6.00% by mass or less, Fe: 0% by mass or more and 10.00% by mass or less, Ni: 0% by mass or more and 10.00% by mass or less, and Mo: 0% by mass or more and 15.00% by mass or less Contains The balance is Co and unavoidable impurities, The alloy has a metal structure including a matrix in which Cu forms a solid solution, The powder has a ratio Pcu of Cu dissolved in the matrix of 1.5 mass % or more and 3.5 mass % or less.

Citation Information

Patent Citations

  • Alloy powder for building up of powder

    JP1987033090A

  • Composite cylinder for plastic molding apparatus

    JP1987273820A

  • Welding rod

    JP1995236992A

  • Valve with corrosion-resistant and wear-resistant alloy joined therewith

    JP2001288521A

  • WELDING Co-BASED ALLOY, WELDING MATERIAL, AND PADDING METALLIC COMPONENT

    JP2016007632A